Exploring the live experiences of the nursing faculty, working in public sector institutions of Punjab regarding educational transformation from diploma to degree programme - Mushtaq, Rahila; Mansoor Ghani; Naveeda Iqbal; Samina Kausar; Misbah Hanif; Sumera Jabeen (Journal of the Pakistan Medical Association, 2024)
The objective of the study was to explore the faculty’s views regarding nursing education transformation from diploma to degree programme. Phenomenological descriptive qualitative approach was adopted to explore the experiences of 10 nursing faculty members who were teaching for more than two years in two public sector nursing colleges (inclusion criteria) in Punjab—College of Nursing, Jinnah Hospital Lahore, and College of Nursing, Nishtar Hospital, Multan—from 2021 to 2022. Data was collected by in-depth interviews of the 10 participants. It was tape recorded, transcribed, and analysed by using Braun and Clarke`s thematic analysis technique. Seven themes were derived, in which good transition, change in instructional methodology, several strengths of degree programme, higher authorities’ ignorance, lack of resources, resources can be managed at government level as well as institutional level, positive impact, improved skills in all dimensions were the main elements. —Continue